Acute lymphoblastic leukemia cells are sensitive to disturbances in protein homeostasis induced by proteasome deubiquitinase inhibition - Mazurkiewicz, Magdalena (Oncotarget, 2017)
The non-genotoxic nature of proteasome inhibition makes it an attractive therapeutic option for the treatment of pediatric malignancies. We recently described the small molecule VLX1570 as an inhibitor of proteasome deubiquitinase (DUB) activity that induces proteotoxic stress and apoptosis in cancer cells. Here we show that acute lymphoblastic leukemia (ALL) cells are highly sensitive to treatment with VLX1570, resulting in the accumulation of polyubiquitinated proteasome substrates and loss of cell viability. VLX1570 treatment increased the levels of a number of proteins, including the chaperone HSP70B’, the oxidative stress marker heme oxygenase-1 (HO-1) and the cell cycle regulator p21(Cip1). Unexpectedly, polyubiquitin accumulation was found to be uncoupled from ER stress in ALL cells. Thus, increased phosphorylation of eIF2α occurred only at supra-pharmacological VLX1570 concentrations and did not correlate with polyubiquitin accumulation. Total cellular protein synthesis was found to decrease in the absence of eIF2α phosphorylation. Furthermore, ISRIB (Integrated Stress Response inhibitor) did not overcome the inhibition of protein synthesis. We finally show that VLX1570 can be combined with L-asparaginase for additive or synergistic antiproliferative effects on ALL cells. We conclude that ALL cells are highly sensitive to the proteasome DUB inhibitor VLX1570 suggesting a novel therapeutic option for this disease.